Relationship Between Non–High-Density Lipoprotein Cholesterol and Coronary Heart Disease (Medical Forum Monthly, 2021)
Objective: To study the association between lipoprotein cholesterol not of high density and stenosis of the coronary artery demonstrated by the coronary angiography.Study Design: Prospective and cross-sectional studyPlace and Duration of Study: This study was conducted at the National Institute of Cardiovascular Diseases Karachi from December 2019 to November 2020.Materials and Methods: In three subsets, we compared the non-high-density cholesterol level and coronary heart disease. Spearman's correlation has been applied to analyze the correlated non-high-density cholesterol lipoprotein and coronary heart disease.Results: The cholesterol -lipoprotein-high-density rate was higher in the group of coronary artery disorders compared with the group of the non-coronary artery (P < 0.01). The analytical correlation of Spearman demonstrated that a strong association between non-high-density lipoprotein and SYNTAX score (r=0.071, P<0.001; r=0.316, P<0.001) was observed. In multivariate logistic regression analysis, the indigenous predictor of coronary artery condition was non–high density lipoprotein cholesterol high density lipoprotein cholesterol ratio, (Odds ratio: = 3,645; = 2.096; 95% confidence interval; = 1.438–3.054).Conclusions: The ratio of non–high-density lipoprotein cholesterol was associated with the severity of coronary artery disease, suggesting that it might be utilized as a biomarker.